2004
DOI: 10.4067/s0034-98872004000500005
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico y clínico de la invaginación intestinal en lactantes de la Región Metropolitana

Abstract: IS incidence rates were intermediate compared to other series, stable over time, and similar between the public and private sector. Clinical characteristics were similar to those previously reported with a disproportionately high use of surgical correction over enema, currently considered the preferred treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
1
0
3
Order By: Relevance
“…A study of ten African countries showed that 90 per cent of infant intussusceptions required surgery. Operative proportions were similarly high in studies from other LMICs. Death from intussusception is rare in HICs, usually less than 1 per cent.…”
Section: Resultsmentioning
confidence: 68%
“…A study of ten African countries showed that 90 per cent of infant intussusceptions required surgery. Operative proportions were similarly high in studies from other LMICs. Death from intussusception is rare in HICs, usually less than 1 per cent.…”
Section: Resultsmentioning
confidence: 68%
“…Los síntomas más frecuentes son dolor abdominal, diarrea en "jalea de grosella", masa palpable en el flanco derecho, irritabilidad, entre otros (1) . La ecografía como método diagnóstico tiene un 100 % de sensibilidad y 88-100 % de especificidad (7) . Sus principales hallazgos son: imagen de una masa ovalada con anillo periférico hipoecogénico y ecogenicidad central conocido como el signo de la diana (corte axial) que representa las paredes intestinales y el mesenterio invaginado; mientras, el Doppler evalúa la hiperemia de las paredes periféricas del asa invaginada versus la ausencia de flujo sugestiva de isquemia (8) .…”
Section: Introductionunclassified
“…A medida que progresan los síntomas, se desarrolla un estado de letargia creciente, lo que también plantea como diagnóstico diferencial cuadros de compromiso neurológico o séptico. No obstante, la frecuencia de los síntomas es variable: la tríada clásica sólo se describe en un 15% a 30% de los pacientes 7 , mientras que un 10% de los lactantes pueden no tener signos de dolor evidente 7 .…”
Section: Introductionunclassified
“…En lactantes, la mayoría de los casos son idiopáticos 7 , sólo en un 2-8% de los pacientes se demuestran alteraciones anatómicas que actúan como causantes de la intususcepción 4,6 , siendo la más frecuente el divertículo de Meckel, especialmente en mayores de 2 años y adultos 2,4 .…”
Section: Introductionunclassified